2020
DOI: 10.1080/11101849.2020.1762281
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the effect of recruitment maneuvers and positive end-expiratory pressure on diaphragmatic functions in obese patients undergoing laparoscopic sleeve gastrectomy: A randomized controlled study

Abstract: 2020) Ultrasonographic evaluation of the effect of recruitment maneuvers and positive end-expiratory pressure on diaphragmatic functions in obese patients undergoing laparoscopic sleeve gastrectomy: A randomized controlled study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The reasons for the 183 exclusions were as follows: 105 were non-RCTs, 7 were non-adult studies, 18 reported open abdominal surgery, 13 did not report PPCs, 33 were animal experiments and 7 did not compare recruitment maneuvers to conventional mechanical ventilation. Finally, 17 RCTs with a total of 3480 patients were examined [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The details of the included studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reasons for the 183 exclusions were as follows: 105 were non-RCTs, 7 were non-adult studies, 18 reported open abdominal surgery, 13 did not report PPCs, 33 were animal experiments and 7 did not compare recruitment maneuvers to conventional mechanical ventilation. Finally, 17 RCTs with a total of 3480 patients were examined [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The details of the included studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the completeness of the outcome data and lack of selective reporting, the risks of attrition bias and reporting bias were likewise evaluated as low. Five trials did not provide information on allocation concealment [ 18 , 26 , 28 , 31 , 32 ]. Twelve studies did not report the blinding of the outcome evaluators [ 15 , 18 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations